Modifiable risk factors for inflammatory bowel disease in Kuwait: A cross-sectional analysis - Reem Alhasan; Talal Alshatti (PLoS ONE, 2025)
Inflammatory bowel disease (IBD), a lifelong inflammatory condition of the gastrointestinal tract, is influenced by complex interactions between genetics and environmental exposures. While IBD rates have increased globally, largely due to Westernized lifestyle shifts, the contributors to IBD in Kuwait remain poorly understood. This cross-sectional study aimed to explore lifestyle, dietary, and occupational exposures associated with IBD in this unique population. A total of 520 adults (412 with IBD and 108 without IBD) completed a 40-item online questionnaire assessing early-life, lifestyle, occupational, and dietary exposures. Of the IBD participants, 174 had ulcerative colitis (UC) and 238 had Crohn’s disease (CD). The questionnaire was adapted from a previously validated tool, but was not formally validated in the Kuwaiti population. Associations between these factors and IBD status were analyzed using multivariable logistic regression with adjusted odds ratios (AORs) and 95% confidence intervals (CIs) reported after adjusting for potential confounders. Factors associated with increased odds of IBD included male sex (AOR = 2.487, p = 0.005), younger age (AOR = 0.964, p = 0.004), positive family history (AOR = 2.141, p = 0.023), mentally demanding jobs (AOR = 1.818, p = 0.039), alcohol consumption (AOR = 6.508, p = 0.016), frequent spicy food intake 1–2 times/week (AOR = 2.631, p = 0.008), and prior parasitic infection (AOR = 0.484, p = 0.042). A history of appendectomy was also associated (AOR = 7.158, p = 0.003). Several modifiable exposures were found to be associated with IBD status in Kuwait. These findings underscore the multifactorial nature of IBD. However, the cross-sectional design, reliance on self-reporting, and use of a non-validated instrument limit causal interpretation. Future longitudinal research is needed to better understand temporal relationships.